1977
DOI: 10.1007/bf00225666
|View full text |Cite
|
Sign up to set email alerts
|

Special dendritic and axonal endings formed by the cerebrospinal fluid contacting neurons of the spinal cord

Abstract: The cerebrospinal fluid (CSF) contacting neurons have a dendritic process which protrudes into the central canal, and is provided with one long kinocilium and many shorter stereocilia (about 80 in the turtle) as revealed by scanning electron mecroscopy. The shape, number and arrangement of the cilia are similar to those of known receptor endings. The silver impregnated axons of these cells converge to a paired centrosuperficial tract forming terminal enlargements at the ventrolateral surface of the spinal cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 8 publications
4
38
0
Order By: Relevance
“…Such neurons display similar morphological characteristics in many vertebrate species ranging from cyclostomes to mammals (18,19), and the possibility that they represent a separate spinal neurosecretory system has been suggested (19). Our findings support this view and strongly suggest that, at least in the sucker, the central-canal CSF-contacting IR-UII neuronal system may have provided a biosynthetic identity to the above quoted neurons.…”
Section: Discussionsupporting
confidence: 81%
“…Such neurons display similar morphological characteristics in many vertebrate species ranging from cyclostomes to mammals (18,19), and the possibility that they represent a separate spinal neurosecretory system has been suggested (19). Our findings support this view and strongly suggest that, at least in the sucker, the central-canal CSF-contacting IR-UII neuronal system may have provided a biosynthetic identity to the above quoted neurons.…”
Section: Discussionsupporting
confidence: 81%
“…S1J-N). Whole-cell GFP labeling identified these cells as the cerebrospinal fluidcontacting neurons of the central canal (CSF-cNs) VighTeichmann, 1971, 1998;Vigh et al, 1977;Stoeckel et al, 2003;Marichal et al, 2009) (Fig. 1J-M).…”
Section: Resultsmentioning
confidence: 99%
“…Those settled in the lateral wall account for 73±6% of CSF-cNs at P0 (Fig. 1J,K Although spinal CSF-cNs have been described in a wide number of vertebrate species (Vigh and Vigh-Teichmann, 1971;Vigh et al, 1977Vigh et al, , 1983Stoeckel et al, 2003;Marichal et al, 2009;Huang et al, 2006;Djenoune et al, 2014;Jalalvand et al, 2014), their characteristics remain to be fully clarified. We evaluated the expression of distinct cellular markers and found that CSF-cNs express high levels of Nkx6-1 and Sox2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations